Weight change in middle adulthood and breast cancer risk in the EPIC‐PANACEA study. Issue 12 (16th May 2014) - Emaus, Marleen J.; van Gils, Carla H.; Bakker, Marije F.; Bisschop, Charlotte N. Steins; Monninkhof, Evelyn M.; Bueno‐de‐Mesquita, H. B(as); Travier, Noémie; Berentzen, Tina Landsvig; Overvad, Kim; Tjønneland, Anne; Romieu, Isabelle; Rinaldi, Sabina; et al.
<x xml:space="preserve">Abstract</x> Long‐term weight gain (i.e., weight gain since age 20) has been related to higher risk of postmenopausal breast cancer, but a lower risk of premenopausal breast cancer. The effect of weight change in middle adulthood is unclear. We investigated the association between weight change in middle adulthood (i.e., women aged 40–50 years) and the risk of breast cancer before and after the age of 50. We included female participants of the European Prospective Investigation into Cancer and Nutrition cohort, with information on anthropometric measures at recruitment and after a median follow‐up of 4.3 years. Annual weight change was categorized using quintiles taking quintile 2 and 3 as the reference category (−0.44 to 0.36 kg/year). Multivariable Cox proportional hazards regression analysis was used to examine the association. 205, 723 women were included and 4, 663 incident breast cancer cases were diagnosed during a median follow‐up of 7.5 years (from second weight assessment onward). High weight gain (Q5: 0.83–4.98 kg/year) was related to a slightly, but significantly higher breast cancer risk (HRQ5_versus_Q2/3: 1.09, 95% CI: 1.01−1.18). The association was more pronounced for breast cancer diagnosed before or at age 50 (HRQ5_versus_Q2/3: 1.37, 95% CI: 1.02−1.85). Weight loss was not associated with breast cancer risk. There was no evidence for heterogeneity by hormone receptor status. In conclusion, high weight gain in middle adulthood increases the risk of breast cancer. The association seems to be more pronounced for breast cancer diagnosed before or at age 50. Our results illustrate the importance of avoiding weight gain in middle adulthood.